24.6k views
1 vote
8(x−6)=3(2x−1)+2x−45

2 Answers

3 votes

Any number works!

Let's solve your equation step-by-step.

8(x−6)=3(2x−1)+2x−45

Step 1: Simplify both sides of the equation.

8(x−6)=3(2x−1)+2x−45

(8)(x)+(8)(−6)=(3)(2x)+(3)(−1)+2x+−45(Distribute)

8x+−48=6x+−3+2x+−45

8x−48=(6x+2x)+(−3+−45)(Combine Like Terms)

8x−48=8x+−48

8x−48=8x−48

Step 2: Subtract 8x from both sides.

8x−48−8x=8x−48−8x

−48=−48

Step 3: Add 48 to both sides.

−48+48=−48+48

0=0

User Exta
by
4.8k points
5 votes

Answer:

any value of x will satisfy this equation

Explanation:

8x -48 = 6x -3 +2x -45

8x -48 = 8x -48 . . . . . . . . . . a tautology. Any x will satisfy.

User Psv
by
4.9k points